Genski inženiring lignina - Ulčnik, Ajda (Les (Ljubljana), 2010)
Trends towards reducing the use of non-renewable resources and substituting them with renewable resources, such as wood, are emerging in developed countries. Wood is an environmentally friendly and renewable material. The demand for wood and wooden products has been growing, resulting in deforestation of large areas around the world. The solution might be the use of transgenic trees, which could produce more wood in the same land area. Exploiting biotechnological applications also makes it possible to improve the properties of wood. The paper reviews accomplishments in forest biotechnology, particularly the properties of genetically modified trees and their wood.
Keywords: biotechnology; biotehnologija; genski inženiring; drevesa; les; lignin